Examining factors affecting students's choice of Islamic institutions: a survey of International students at International Islamic University Malaysia - Olayemi, Saheed Aliu (Institute of Education, International Islamic University Malaysia, 2011)
Students' choice of higher educational institution which its values align with student and the parents' religious background has been given more attention. This study therefore examined some of the factors affecting international students' choice of Islamic educational institution such as International Islamic University Malaysia. The examined factors in this study were religious academic programme, Islamization of knowledge, Islamic culture and environment, Muslim parent, the image and reputation of the institution, institutional facilities, cost of study and financial aid. A total number of 311 international students were surveyed using a convenient sampling method. A Principal Component Analysis was used to identify the underlying factors of international students' choice of International Islamic University Malaysia. Also, descriptive statistics such as percentages and mean and Independent sample T-test were used to analyze other research questions. The result of the Principal Component Analysis shows that, seven factors affect international students' choice of International Islamic University Malaysia with the exception of Religious Academic Programme. However, Islamization of knowledge and Islamic environment and culture were the most influential factors identified by the international students. It was found also that there are no significant differences between international male and female students in their influential factors of International Islamic University Malaysia except in the image and reputation of the institution, institutional facilities and cost of study. Finally, the result shows that non religious factors such as the cost of study, image and reputation of the institution and institutional facilities play a greater role in international student's choice of International Islamic University Malaysia. Thus, the researcher will like to suggest that both the religious and non religious factors identified by the international students should be given much more attention by continue improving it.